Exercise Interventions for Reducing Low Back Pain During Pregnancy: A Scoping Review of Randomized Controlled Trials - Yeni Hendriyanti; Arifin Triyanto (STIKep PPNI Jawa Barat, 2026)
Background: Low Back Pain (LBP) can have a negative impact on physical and psychological conditions, so that treatment of these symptoms requires attention. There is a lot of literature stating the positive effects of exercise activity, but evidence related to the type and duration of activity is not clear. Objective: This study aims to find out the type and duration of exercise that can reduce LBP during pregnancy. Methods: Scoping review using the framework from Arksey & O'Malley consisting of: identifying research questions; identifying relevant studies; study selection; charting the data; and collating, summarizing and reporting the results. Searching for articles using databases from Sciencedirect, Pubmed, Springer link, Scopus, Clinicalkey, Oxford Academic .The inclusion criteria: full text in English, published in 2020 until 2025, experimental RCT research design, nursing scope. Article appraisal using CONSORT from the Joana Briggs Institute (JBI) independently by each author. Results: Five randomized controlled trial articles were included according to the criteria. Physical activities that can be done to reduce LBP symptom include pilates (2 times a week for 60 minutes); aerobic exercise (3 times a week for 60 minutes); lumbar stabilization exercise (2 times a week for 50 minutes) and pelvic floor muscle (3 times a week for 60 minutes). All of the above activities have a positive effect on reducing pain felt by pregnant women at various gestational ages. Conclusion: In conclusion, LBP during pregnancy can be reduced by physical activity exercises such as Pilates, aerobics, lumbar stabilization exercises or pelvic muscle floor exercises with an average duration of 2 times a week for 60 minutes